Implementation of Islamic Literacy in Strengthening Reading Interest of Grade III Students at Nurul Qodiri Integrated Islamic Elementary School: The Perspective of Nurcholish Madjid's Thought - Elfi Sa’adah; Rina Mida Hayati; M. Sayyidul Abrori (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2026)
Literacy is a crucial indicator in determining the quality of education, encompassing not only the ability to read and write but also the capacity to understand and critically analyze information. In the Islamic perspective, literacy has a spiritual dimension rooted in the command of iqra’; however, its implementation in primary education institutions still faces various challenges, particularly the low level of students’ reading interest. This phenomenon is also found at MIS Terpadu Nurul Qodiri, where literacy activities have not optimally fostered students’ reading interest. This study aims to analyze the implementation of Islamic literacy in strengthening the reading interest of third-grade students from the perspective of Nurcholish Madjid’s thought. This research employs a qualitative approach with a field research design. The research subjects include the principal, teachers, students, and parents, who were selected purposively. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing, with validity ensured through triangulation techniques. The findings reveal that the implementation of Islamic literacy has been carried out through habitual activities such as reading the Qur’an and Islamic texts before learning begins; however, it has not been optimal in improving students’ reading interest. This is due to the lack of systematic planning, limited availability of engaging literacy media, and monotonous teaching methods. In addition, program evaluation has not been conducted in a structured manner and does not yet reflect the humanistic approach proposed by Nurcholish Madjid, which emphasizes the development of critical awareness, active student participation, and contextual learning. Therefore, it is necessary to develop a more innovative, structured, and sustainable Islamic literacy program to enhance students’ reading interest and foster a critical and reflective literacy culture